2010
DOI: 10.1097/jto.0b013e3181c20080
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Local and Distant Failure in Resected Lung Cancer: Implications for Reported Rates of Local Failure

Abstract: The time interval from surgery to either local or distant failure is not significantly different. Patterns of failure analyses in which only first sites of failure are scored will underestimate the frequency of local recurrence. Nevertheless, the magnitude of this error is expected to be small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 14 publications
1
39
0
1
Order By: Relevance
“…Recurrence time from surgery in this cohort is within the range reported previously [32,33] and survival outcome is consistent with other studies. [6,32] Of interest, in this female cohort, mutated EGFR was associated with poor survival after recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…Recurrence time from surgery in this cohort is within the range reported previously [32,33] and survival outcome is consistent with other studies. [6,32] Of interest, in this female cohort, mutated EGFR was associated with poor survival after recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that some patients may experience recurrence in the future. Boyd et al [43] recently reported that median time to recurrence in resected NSCLC was 13 months, with 75% of documented disease recurrence occurring in less than 2 years. With postsurgical follow-up greater than 2 years in 76% of our cohort, we suggest that additional disease recurrence is likely to be very low.…”
Section: Limitationsmentioning
confidence: 97%
“…However, 30% to 55% of patients with NSCLC develop recurrence and die of their disease despite curative resection. While recurrence most commonly occurs at distant sites [93], there has also been a report concerning the underestimation of the frequency of local recurrence [94]. There is an urgent need for the identification of new predictive factors to improve long-term survival rates.…”
Section: Mirna As a Noninvasive Predictor For Recurrence And Survivalmentioning
confidence: 99%